’’نقشِ فریادی‘‘ کا اسلوبیاتی تجزیہ - Khayaban; •ڈاکٹر احمد ولی; • ڈاکٹر امجد امید; صاحب خان (Khayaban - خیابان, 2025)
Faiz Ahmad Faiz is considered as one of the great poets of Urdu. His unique style has played a big role in his immense fame and popularity .His childhood and boyhood were influenced by romanticism while his young age was devoted to the progressive movement. That is why there is a profound effect of romance and progressivism on the subjects as well as their style. In the article under review, an attempt has been made to bring out the features of his style and different aspects in the context of “Naqsh-e-Faryadi